ANALISIS FRAMING: KONSTRUKSI PEMBERITAAN ISLAM DAN POLITIK PADA HARIAN AMANAH 2017 - Karim, Syahrir; Alamsyah, Anggriani (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2018)
Starting from proposition of ‘Inna Al-Islam Ad-Dinn wa Ad-dawlah’ that Islam does not only discuss religion but also the country. In this circumstance, Islam will always display new political forces with Islamic social origin such as religious social organizations in the form of civil society. Amanah Tabloid is having an ideological emotional closeness with certain organizations, so that, this Amanah Tabloid as a media of propaganda will be greatly affected by ideological closeness in the framing pattern of the news. This research seeks to look at the construction patterns of Amanah Tabloid coverage related to Islam and Politics and see in depth the influence of the news framing on Islamic social movements as well. Relevant theories in this study include Islamism, Islamic social movements and media framing.